Gestión del comportamiento en el aprendizaje virtual en los niños de preescolar en Instituciones Educativas del Cantón San Miguel, Provincia Bolívar, en el año - Moyano Verdezoto, Tania Marlene (2023)
This study examines how the coronavirus pandemic has changed the way educational institutions teach and learn, moving from the traditional classroom to the virtual classroom. Various authors point out the advantages of virtual education, and also highlight the importance of managing an environment of respect and cooperation, in such a situation the educational units of the canton of San Miguel de Bolívar, raise various questions: How can teachers promote mutual respect? establish clear and consistent limits, create an environment of respect and cooperation, use positive reinforcement, and be patient and understanding with students? To address this problem, an investigation was carried out to analyze behavior management in learning virtual in preschool children through a mixed methodology with a finite population of 197 education professionals and parents. A survey instrument with a four-point Likert scale was used to assess children's virtual learning behavior management. The results indicate that the majority of those surveyed considered that the workspace intended for receiving virtual classes was adequate, although a small group did not have access to a suitable environment. In addition, the majority considered that virtual education has had a positive influence on the behavior and development of children's abilities and skills. However, the negative effects such as increased exposure to the blue screen and lack of social interaction stand out. In conclusion, it is important that teachers, parents, and mental health professionals work together to ensure that children receive the benefits of virtual education without suffering the negative effects